ANALYSIS OF QUALITY OF SERVICE BANDWIDTH MANAGEMENT ON COMPUTER NETWORK USING MIKROTIK RB951Ui-2HnD - I Made Arya Budhi Saputra; Putu Dicky Indrajaya; Ricky Aurelius Nurtanto Diaz; I Komang Agus Ady Aryanto; Ni Luh Putri Srinadi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
Computer networks are now part of every human activity. The use of computer networks is currently experiencing a significant increase due to the Covid-19 pandemic, however, there are still many problems with computer networks, such as what often happens is the slow pace of computer networks in transferring data caused by limited bandwidth or maximum limits. owned by the computer network. For that, we need a computer network bandwidth management method called the QoS (Quality of Service) method. In this method, a tool called the Mikrotik Router-board RB951Ui-2HnD is used to conduct this research. In implementing this system the steps are taken starting from data collection, requirements analysis, system design with flowcharts and system depiction using a star topology, then implementation and unit testing on the user or Client, and testing the computer network system on the Mikrotik Router-board. The results of this study will be explained using statistical tables obtained from testing using the Wireshark application